2010
DOI: 10.1111/j.1460-9568.2010.07313.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of binaural masking level difference in the inferior colliculus of the barn owl (Tyto alba)

Abstract: Humans and animals are able to detect signals in noisy environments. Detection improves when the noise and the signal have different interaural phase relationships. The resulting improvement in detection threshold is called the binaural masking level difference. We investigated neural mechanisms underlying the release from masking in the inferior colliculus of barn owls in low-frequency and high-frequency neurons. A tone (signal) was presented either with the same interaural time difference as the noise (maske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 62 publications
3
11
0
Order By: Relevance
“…Nodes tuned to smaller ITDs responded most to in-phase tones (So) and least to out-of-phase tones (Sπ), and vice-versa for nodes tuned to larger ITDs. studies have reported neural responses consistent with a cross-correlation mechanism 15,16,38,39 ( Fig. 3g-i).…”
Section: Network Dynamics Match Those Of a Cross-correlation Mechanismsupporting
confidence: 61%
See 2 more Smart Citations
“…Nodes tuned to smaller ITDs responded most to in-phase tones (So) and least to out-of-phase tones (Sπ), and vice-versa for nodes tuned to larger ITDs. studies have reported neural responses consistent with a cross-correlation mechanism 15,16,38,39 ( Fig. 3g-i).…”
Section: Network Dynamics Match Those Of a Cross-correlation Mechanismsupporting
confidence: 61%
“…Comparative outputs from a simple binaural cross-correlation algorithm (namely for signals in noise passed through narrow-band filters centered at 500 Hz) are shown in Figure 3d-f , and were found to resemble responses across the DNN’s layer 2 nodes (Pearson’s r=0.36, p≪0.0001). A number of physiology studies have reported neural responses consistent with a cross-correlation mechanism 15,16,38,39 ( Fig. 3g-i ).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In animals, BRM is observed in single neurons at the level of the inferior colliculus (Asadollahi et al, 2010; McAlpine et al, 1996; Palmer et al, 2000) and auditory cortex (Gilbert et al, 2015). In humans, EEG studies reveal larger magnitude for the S0Nπ condition relative to S0N0 for cortical transient components N1–P1–P2 (Fowler & Mikami, 1996; Kevanishvili & Lagidze, 1987), cortical steady-state response (Wong & Stapells, 2004) and brainstem frequency following response (Wilson & Krishnan, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell recordings from a number of animal species have shown that the initial interaural processing important for the BMLD takes place in the medial superior olive and that an accurate representation of this processing is preserved at the level of the inferior colliculus (IC) ( Asadollahi et al 2010 ; Palmer and Shackleton 2002 ; Shackleton and Palmer 2010 ). Indeed, it has proven possible to provide a quantitative account of the BMLD based solely on changes in the firing rates in cells of the central nucleus of the IC ( Palmer and Shackleton 2002 ).…”
mentioning
confidence: 99%